Telegram from Marianne Homburger to Max Bredig, December 19, 1938 - Homburger, Marianne (1938)
Marianne Homburger (1903-1987) informs her brother, Max Bredig (1902-1977), that she received an affidavit from Otto Warburg.
Keywords: Homburger, Marianne, 1903-1986; Western Union Telegraph Company; Third Reich; Bredig, Max Albert, 1902-1977